Paralithocins, Antimicrobial Peptides with Unusual Disulfide Connectivity from the Red King Crab, Paralithodes camtschaticus - Moe, Morten Kaare; Haug, Tor; Sydnes, Magne Olav; Sperstad, Sigmund; Li, Chun; Vaagsfjord, Lena Christine; de la Vega, Enrique; Stensvåg, Klara (Journal of Natural Products, 2018)
Submitted manuscript version. Published version available at https://doi.org/10.1021/acs.jnatprod.7b00780 . With permission from Moe, M.K., Haug, T., Sydnes, M.O., Sperstad, S.V., Li, C., Vaagsfjord, L.C., . Stensvåg, K. (2018). Paralithocins, Antimicrobial Peptides with Unusual Disulfide Connectivity from the Red King Crab, Paralithodes camtschaticus . Journal of natural products, 81 (1), 140-150. Copyright 2018 American Chemical Society. As part of an ongoing exploration of marine invertebrates as a source of new antimicrobial peptides, hemocyte extracts from the red king crab, Paralithodes camtschaticus , were studied. Three cationic cysteine (Cys)-rich peptides, named paralithocins 1–3, were isolated by bioassay-guided purification, and their amino acid sequences determined by Edman degradation and expressed sequences tag analysis. Disulfide bond mapping was performed by high-resolution tandem mass spectrometry. The peptides (38–51 amino acids in length) share a unique Cys motif composed of eight Cys, forming four disulfide bridges with a bond connectivity of (Cys relative position) Cys1–Cys8, Cys2–Cys6, Cys3–Cys5, and Cys4–Cys7, a disulfide arrangement that has not been previously reported among antimicrobial peptides. Thus, paralithocins 1–3 may be assigned to a previously unknown family of antimicrobial peptides within the group of Cys-rich antimicrobial peptides. Although none of the isolated peptides displayed antimicrobial activity against the target strains Escherichia coli, Pseudomonas aeruginosa , or Staphylococcus aureus , they inhibited the growth of several marine bacterial strains with minimal inhibitory concentrations in the 12.5–100 μM range. These findings corroborate the hypothesis that marine organisms are a valuable source for discovering bioactive peptides with new structural motifs.